Development on Employee Performance with Motivation as a Moderating Variable - Diansyah Diansyah; Abal Falih Harsy (CV. Tripe Konsultan, 2025)
This research aims to analyze the influence of job satisfaction and human resource development on employee performance with motivation as a moderating variable . The research method used was quantitative with a survey approach involving 125 employees PT. Laut Makmur Sentosa as a sample. Data analysis using Smart PLS (Partial Least Square) software. The research results show that job satisfaction has a significant effect on employee performance, human resource development has a significant effect on employee performance, motivation has a significant effect on employee performance . Furthermore, motivational moderation can strengthen the influence Job satisfaction and vice versa weaken motivation moderation the influence of job satisfaction on employee performance. The implications of this research provide valuable insight for companies in designing effective strategies to improve employee performance.